ANALISIS KELAYAKAN FINANSIAL PENDIRIAN INDUSTRI VANILIN DENGAN BAHAN BAKU VANILI BASAH (Vanilli spp) - Kirana Sasmitaloka; nina Jusnita; akbar Andayani (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
Vanilla processing industry is one of the agro-processing of dried vanilla into vanilla extract. Vanilla industry designed to provide added value for vanilla. The aims of this research is to know financial feasibility of curing vanilla applied on an industrial scale. Calculation of the investment criteria of business feasibility studies vanilla using a modified curing is obtained Net Present Value Rp 1.089.999.998,00, IRR 58,46%, Net Benefit Cost Ratio 1,01, and Pay Back Period for 2,44 years. Based on these parameters, it can be concluded that the design of the vanilla industry is feasible to operate.Keywords: Vanilla, vanillin, financial feasibility, industry